Effects of ethanolic extract of green tea on decreasing the level of lipid profile in rat - Farjad Amanolahi; Hasan Rakhshande (Mashhad University of Medical Sciences, 2012)
Objective: The aim of the present study was to elucidate the possible biochemical improving effect in lipid metabolic that may result from continuous treatment with Green Tea extract in normal albino rats and those rendered hyperlipidemic by long term supplementation of fat-enriched diet. Materials and Methods: Fifty male albino rats aged six weeks with 200±10 g weight were randomly divided into five groups: Group A (negative control), groups B (positive control), Group C (treatment with drug), Group D (treatment with extract), and Group E (prevention with extract). All groups except Group A were received fat-enriched diet throughout the study. Group C received 25 mg/kg/day of the nicotinic acid from day 28 to the end of study. Group D was also treated with 100 mg/kg/day of the extract from day 28 to the end of study and finally group E was also treated with 100 mg/kg/day of the extract from the start of the study to the end. Lipid levels were determined weekly. Data were expressed as mean±SEM which were calculated using SigmaPlot® software. The obtained data were statistically analyzed using Student's t-test. Results: In group (D), total cholesterol, LDLc, HDLc, and triglyceride levels were significantly decreased by 33.3%, 30.2%, 40%, respectively, compared with the group C (pConclusion: The results of this study demonstrated that the extract of green tea has a hyperlipidemic lowering effect.